V-056 LAPAROSCOPIC VENTRAL HERNIA REPAIR WITH GORE SINECOR INTRAPERITONEAL BIOMATERIAL: OUR CENTER EXPERIENCE. (13th October 2022) - Monti, E; Latham, L; Gianazza, S; Zullo, A; Odeh, M; Colombo, E M; Marzorati, A; Fanelli, M; Costa, J; Inversini, D; Ietto, G; Carcano, G
Abstract: Aim: Ventral hernias including incisional ones are very common in our population. Mesh reinforcement options for ventral/incisional hernia repair continue to evolve with advances in polymer science and better understanding of the extracellular matrix. Consensus on the safety and efficacy of these various types of synthetic and biologic mesh has yet to be reached. Intraperitoneal onlay mesh (IPOM) is the laparoscopic technique most frequently used in our center to treat umbilical and abdominal ventral defects sized 3 cm to 8 cm. Our equipe built an expertise with Gore DualMesh prosthesis (2% recurrence ratio in our center); we used the Gore Sinecor Intraperitoneal Biomaterial for the first time here. Methods: Symptomatic supraumbilical incisional hernia in a 74 years old man; parietal defect sized 7×8 cm. We performed an Ipom repair procedure using a 20×25 cm Gore Sinecor Intraperitoneal Biomaterial, trimmed to 18×20 cm. Follow-up at one and six months from surgery. Results: The patient was discharged the day after surgery. He did not complain severe pain in the first week after surgery and he only use Paracetamolo 1g die as antalgic therapy. After seven days he resumed his daily activities. He did not experience any short-term sieroma nor long-term complication at follow up. Conclusions: The Gore Sinecor Intraperitoneal Biomaterial, while maintaining a firm peritoneal adhesivity, has a better handling and feels lighter than the Gore DualMesh we routinely use. The transparency makes it possible to visualize the overlying abdominal wall, allowing a safer tacs positioning.